Comparative Characteristics of Morphometric Parameters of Achenes (Seeds) for Adenocaulon Adhaerescens Maxim. (Asteraceae) in Native and Secondary Distribution Ranges - Vinogradova, Yulia; Gorbunov, Yuri (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
Adenocaulon adhaerescens Maxim. is the potentially medicinal species with high antioxidant activity. Morphometric characteristics of achenes (seeds) for the species have been studied in four populations of native distribution range in Primorsky Krai (Russia). The distance from the southernmost (Popova Island) to the northernmost (buffer zone of the Ussuri Nature Reserve) of the seed collection point is about 100 km, and this, of course, is not enough to identify correlation between geographical latitude and seed size. The environmental conditions in all four habitats are also the same – shaded paths in the forest along streams or wet plots, so that light and moisture do not seem to influence the size of the seeds. Studied plants in the fruiting phase had an average height of 83.9 cm, with 70 % of the main axis being the inflorescence and the number of lateral axes of the inflorescence ranging from 10 to 28. The size of the leaf at the base of the panicle was, on average, 8.8 × 10.6 cm. Plants on Russky Island have reliably smaller achenes (5.4 × 1.9 mm) than in other studied populations (6.7 × 2.3 mm). It was noted that the length and diameter of the achene vary in the native distribution range at a low level (CV = 10–12 %). However, we were surprised to compare our data with ones in the Moscow: in the secondary distribution range, which is almost 9 thousand kilometers away from natural habitats, the average size of seeds of this species has not changed over 70 years of introduction. In the native distribution range, seed productivity of one plant is two to three times higher than in the secondary distribution range formed in the Moscow. This is explained not by the large number of seeds in a head (5–7 seeds), but by the large number of heads formed on the plant (46-77 vr. 25-30 heads).